2021
DOI: 10.3390/toxins13120832
|View full text |Cite
|
Sign up to set email alerts
|

Lonomia obliqua Envenoming and Innovative Research

Abstract: As a tribute to Butantan Institute in its 120th anniversary, this review describes some of the scientific research efforts carried out in the study of Lonomia envenoming in Brazil, a country where accidents with caterpillars reach over 42,000 individuals per year (especially in South and Southeast Brazil). Thus, the promising data regarding the studies with Lonomia’s toxins contributed to the creation of new research centers specialized in toxinology based at Butantan Institute, as well as to the production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 97 publications
0
11
0
1
Order By: Relevance
“…In this regard, the ability of the crude bristle extract of Lonomia obliqua to modulate inflammatory markers was recently demonstrated in a human macrophage model ( Oliveira et al, 2021 ). As Lopap has previously been shown not to exert pro-inflammatory activity ( Fritzen et al, 2005 ; Waismam et al, 2009 ) and, as with Losac, Lopap-derived peptides provide cytoprotective activity ( Chudzinski-Tavassi et al, 2010 ; Carrijo-Carvalho et al, 2012 ; Wlian et al, 2014 ; Alvarez-Flores et al, 2021 ) and improve wound healing ( Sato et al, 2016 ), we investigated the effect of these recombinant proteins in myoblast cells upon inflammatory stimulus by IL-1β. Interestingly, we found that both proteins exerted anti-inflammatory effects: they were able to inhibit the production of PGE 2 and IL-6 induced by IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the ability of the crude bristle extract of Lonomia obliqua to modulate inflammatory markers was recently demonstrated in a human macrophage model ( Oliveira et al, 2021 ). As Lopap has previously been shown not to exert pro-inflammatory activity ( Fritzen et al, 2005 ; Waismam et al, 2009 ) and, as with Losac, Lopap-derived peptides provide cytoprotective activity ( Chudzinski-Tavassi et al, 2010 ; Carrijo-Carvalho et al, 2012 ; Wlian et al, 2014 ; Alvarez-Flores et al, 2021 ) and improve wound healing ( Sato et al, 2016 ), we investigated the effect of these recombinant proteins in myoblast cells upon inflammatory stimulus by IL-1β. Interestingly, we found that both proteins exerted anti-inflammatory effects: they were able to inhibit the production of PGE 2 and IL-6 induced by IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Although the widely used treatment, LAV, produced against L. obliqua has proven to be effective for at least two other Lonomia species [6], it would be important to further explore its efficacy against other species. For example, until 2020, accidents in Colombia with species of Lonomia other than L. achelous were successfully treated with the antivenom produced by the Butantan Institute against L. obliqua and in French Guiana the maximum recommended dose (10 vials) of the same antivenom was used [38],[19]. Thus, there is an opportunity for an integrated initiative leading to the design of treatment protocols in case of accidents with Lonomia , where species identification will be a must, and perhaps the production of a polyvalent treatment that can be used in different countries, as has been proposed for snakebite [39], [40].…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, different types of ion channels and receptors were investigated ( 1 ): voltage-gated sodium channels (rNa v 1.2, rNa v 1.3, rNa v 1.4, mNa v 1.6 and hNa v 1.8) and their auxiliary subunits rβ1 and hβ1 ( 2 ), potassium channels (hK v 1.1, hK v 1.2, hK v 1.3, hK v 11.1 or hERG, dm Shaker -IR, mGIRK1, mGIRK2 and mIRK1) ( 3 ), histamine receptors (hH1R, hH2R, hH3R and hH4R) ( 4 ) bradykinin receptor (hB2R) ( 5 ), cannabinoid receptor (hCB2R) ( 6 ), Mas-related G protein-coupled receptor member X2 (hMRGPRX2) ( 7 ), transient receptor potential channel (hTRPV1) ( 8 ), muscle-type nAChR (hα1β1γδ) ( 9 ), neuronal-type nAChR (hα7) and ( 10 ) acid-sensing ion channel (rASIC1a). For the heterologous expression in oocytes, the plasmids for each channel/receptor were linearized using appropriate restriction enzymes and were transcribed using the T3, T7, or SP6 mMESSAGE mMACHINE transcription kit (Ambion, Austin, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To date, there exist numerous studies on the venom composition of Lonomia and Hylesia caterpillars and some more comprehensive studies show the effect of Latoia consocia venom acting on ion channels (6)(7)(8)(9). Unfortunately, little is known about the cutaneous effects of Automeris caterpillars (10).…”
Section: Introductionmentioning
confidence: 99%